2009
DOI: 10.1007/s11671-009-9494-4
|View full text |Cite
|
Sign up to set email alerts
|

Self Assembly and Properties of C:WO3 Nano-Platelets and C:VO2/V2O5 Triangular Capsules Produced by Laser Solution Photolysis

Abstract: Laser photolysis of WCl6 in ethanol and a specific mixture of V2O5 and VCl3 in ethanol lead to carbon modified vanadium and tungsten oxides with interesting properties. The presence of graphene’s aromatic rings (from the vibrational frequency of 1,600 cm−1) together with C–C bonding of carbon (from the Raman shift of 1,124 cm−1) present unique optical, vibrational, electronic and structural properties of the intended tungsten trioxide and vanadium dioxide materials. The morphology of these samples shows nano-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…The proposed reaction sequence for the production of C:TiO 2 NPs, similar to that proposed by Livage [10] in the production of vanadium ethoxide and Mwakikunga et al [11] in the production of tungsten ethoxide, is as follows: …”
Section: Experimental: Preparation and Characterization Of Carbon Modmentioning
confidence: 92%
“…The proposed reaction sequence for the production of C:TiO 2 NPs, similar to that proposed by Livage [10] in the production of vanadium ethoxide and Mwakikunga et al [11] in the production of tungsten ethoxide, is as follows: …”
Section: Experimental: Preparation and Characterization Of Carbon Modmentioning
confidence: 92%
“…The possible reaction path for the dissolution of WCl 6 in ethanol is described elsewhere. [13] For the preparation of the WO 3 film, the WO 3 solution was spin-coated on FTO-coated glass at 600 rpm for 30 s. After coating, the glass was heated on a hot plate at 100 8C for 1 min. This process was repeated several times to make WO 3 films with various thicknesses, and then the samples were heated in an oven at 500 8C for 2 h. To modify the WO 3 /FTO interfaces, C 70 (12 mg) was dissolved in 1,2-diclorobenzene (1 mL).…”
Section: Methodsmentioning
confidence: 99%
“…The enhancement of the electrocatalytic activity of the WO 3 catalysts by adding carbon black to increase the electrical conductivity has been reported [16]. It has been also found that high ethanol sensitivity can be achieved by doping WO 3 with carbon [48]. Figure 5a gives the CV curves of the WO 3 /C samples with different WO 3 :C mass ratio.…”
Section: Resultsmentioning
confidence: 84%